(untitled) (Entrepreneurship Journal for Finance and Business, 2020)
The study sought to activate the learning dimensions of the organization to become a (learning organization) capable of managing its strategic crises, so learning is the way that preserves its potential and strengthens its capabilities to be more rapid in reaction to successive changes and crises, so if organizations want to be effective in an environment dominated by uncertainty It has to rely on its ability to learn, and the availability of its dimensions will provide it with the ability to manage its strategic crises. Hence, the research problem started through a set of research implications that were: - Is there a correlation relationship between the learning organization and strategic crisis management.? - Is there an effect of the learning organization in strategic crisis management? - Is there a contribution to the dimensions of the learning organization in strategic crisis management.? The research assumed the existence of these dimensions in the researched organizations and how these dimensions affect the organization’s strategic crisis management, in order to achieve a flexible response to the turbulent changes of the crisis, and to achieve these objectives, a set of field-tested hypotheses were formulated by adopting the opinions of the members of the research sample, in order to accurately test the hypotheses and ensure their validity. Relying on a number of statistical methods appropriate for these relationships. The research reached a set of Conclusions which confirmed its hypotheses to show the existence of a positive moral correlation as well as the existence of a moral impact of the learning organization in strategic crisis management. The educational dimensions of the organization as an explanatory variable have been identified 68% of the change in strategic crisis management as a responding variable. To present a set of recommendations aimed at activating the positive relations achieved and indicating the aspects that need to redraw their future paths in the researched organizations in particular and the corresponding organizations in general to confront the multiple crises, especially the (Covid-19) crisis.